ANALISIS PENJAMINAN MUTU FAKULTAS EKONOMI: PENCAPAIAN SASARAN MUTU AKADEMIK DAN KESESUAIAN PROSEDUR AKADEMIK DENGAN STANDAR MUTU ISO 9001:2008 - Kardoyo, Kardoyo (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
The objective of the study was to investigate the achievement of academic quality target and the proper of academic quality procedure in each department at teh Economic Faculty, Semarang State University. The research was done in Accounting, Management, Development Economic, and Economics Education Departments. The respondents were departmentâs leaders, including the Head of Departments. The Secretary of Deparment and The Head of laboratory in each department in each department. The data were collected by quetionnaire based on self-assessment. To identify and explain the achivement of academic quality target and the proper of academic quality procedure in each department, it was used branchmarking and root couse analysis based on the National Standard of Bachelor Study Program Accreditation/ BAN PT:2008 and International Standard SSM ISO 9001:2008. The result of the research gave empirical support that: (1) the achivement of academic quality target on students and graduetes standard was very good at the Accounting Departments; it was good at Management; it was good enough at Economics Education and Development Ecoonomics Departments. (2) the achivement of academic quality target on Human Resources standard was very good Â at the Accounting Department, it was very good at Economics Education Department, and it was good enough at the Development Economics and Management Departments. (3) the achivement of academic quality target in curriculum, learning process, academic situation standard was very good at the Accounting, Management, Development Economics and Economics Education Departments, (4) the achivement quality target on facilities. Amenities and system of academic information standard was very good at the Accounting Department, it was good at the Development Economics and Economics Education and it was good enough at the Management department (5) the proper of academic procedure and the achivement of academic quality ware very good at all departments. Therefore, it is suggested for facultyâs and departmentsâs leader to have committment and give support for the lecturers and employees to hold the academic activities which are appropriete to the quality standard and procedure.